ANALYSIS OF THE IMPLEMENTATION OF THE 2013 CURRICULUM REVIEW OF TEACHER PERFORMANCE AND PROFESSIONALISM AT JUNIOR HIGH SCHOOL 3 BASIDONDO - Sari, Kadek Maya Komala (Universitas Madako Tolitoli, 2021)
This study aims to: Knowing the performance of teachers in SMP Negeri 3 Basidondo. This type of research is a qualitative research, in collecting data using observation, interview and documentation techniques. The data analysis technique used is data reduction, data presentation and conclusion drawing and verification. Analysis of the implementation of the 2013 curriculum in terms of teacher performance at SMP Negeri 3 Basidondo with indicators of the ability to plan and prepare for teaching, mastery of the material to be taught to students, mastery of teaching strategy methods, assignment of assignments to students, ability to manage classes, and ability to conduct assessments and evaluation. Of the six indicators, five of them can be implemented well and one indicator that has not been implemented properly is the indicator of the ability to conduct assessments and evaluations. If viewed from the statements of the informants through observations, interviews, and documentation conducted by researchers need to be improved.